The association of serum irisin with anthropometric, metabolic, and bone parameters in obese children and adolescents - Kim, Shin-Hee; Kim, Sung Eun; Kim, Seulki; Ahn, Moon Bae; Cho, Won Kyoung; Cho, Kyoung Soon; Jung, Min Ho (Frontiers in Endocrinology, 2024)
Background Irisin is an adipomyokine secreted by muscle and adipose cells, and it plays a role in glucose, fat, and bone metabolism. This study aimed to determine the correlation of serum irisin levels with anthropometric, metabolic, and bone parameters in obese children and adolescents. Methods This single-center study included 103 Korean children and adolescents: 54 (52.4%) obese participants with a body mass index (BMI) ≥95th percentile and 49 (47.6%) healthy controls with BMI within the 15th to 85th percentile. Various parameters were measured, including fasting blood glucose, fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR), triglyceride and glucose (TyG) index, lipid profile, alkaline phosphatase (ALP), osteocalcin, and 25(OH)-Vitamin D levels. Bone mineral density (BMD) was measured using dual-energy X-ray absorptiometry (DEXA) in 33 healthy subjects. Results Serum irisin was significantly higher in the obese group than in the control group (mean 18.1 ± 3.5 vs. 16.2 ± 2.0 ng/mL; p = 0.001). Serum irisin level was positively correlated with chronological age (r = 0.28; p = 0.004), height SDS (r = 0.24; p = 0.02), BMI SDS (r = 0.37; p < 0. 001), fasting glucose (r = 0.27; p = 0.007), fasting insulin (r = 0.23; p = 0.03), HOMA-IR (r = 0.21; p = 0.04), osteocalcin (r = 0.27; p = 0.006) and negatively correlated with HDL cholesterol (r = -0.29; p = 0.005). All these correlations were evident in obese subjects but not in healthy subjects. ALP and 25(OH)-Vitamin D were unrelated to irisin levels. Among 33 healthy subjects, total body-less head (TBLH) BMD Z-score was positively correlated with serum irisin (r = 0.39; p = 0.03), osteocalcin (r = 0.40; p = 0.02), fasting insulin (r = 0.39; p = 0.04), and HOMA-IR (r = 0.38; p = 0.047). Conclusion This study demonstrated an association between irisin levels and glucose, lipid, and bone parameters in children and adolescents. Our findings suggest that irisin has a potential role in metabolic disorders and bone health in obese children and adolescents.